2017
DOI: 10.1007/s00221-017-4901-z
|View full text |Cite
|
Sign up to set email alerts
|

When an object appears unexpectedly: anticipatory movement and object circumvention in individuals with and without Developmental Coordination Disorder

Abstract: Obstacles often appear unexpectedly in our pathway and these require us to make adjustments to avoid collision. Previous research has demonstrated that healthy adults will make anticipatory adjustments to gait where they have been told there is the possibility of an obstacle appearing. One population that may find this type of anticipatory movement difficult is individuals with Developmental Coordination Disorder (DCD). The current study considered how individuals with and without DCD adjust to the possibility… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
21
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 14 publications
(25 citation statements)
references
References 33 publications
(35 reference statements)
3
21
1
Order By: Relevance
“…When comparing the use of these preferred strategies, participants showed a preference for shortening of the step when three steps away, but then focusing on changing step width to move the participant away from the obstacle on subsequent steps. These results are in line with previous findings which used the same task in typically developing adults (Wilmut et al, 2017). As with this previous study we saw very few instances of step lengthening, despite this being the preferred adjustment while stepping over an obstacle in healthy adults (Moraes, Allard, & Patla, 2007), older females (Weerdesteyn et al, 2005) and individuals recovering from stroke (Den Otter et al, 2005).…”
Section: Discussionsupporting
confidence: 93%
See 3 more Smart Citations
“…When comparing the use of these preferred strategies, participants showed a preference for shortening of the step when three steps away, but then focusing on changing step width to move the participant away from the obstacle on subsequent steps. These results are in line with previous findings which used the same task in typically developing adults (Wilmut et al, 2017). As with this previous study we saw very few instances of step lengthening, despite this being the preferred adjustment while stepping over an obstacle in healthy adults (Moraes, Allard, & Patla, 2007), older females (Weerdesteyn et al, 2005) and individuals recovering from stroke (Den Otter et al, 2005).…”
Section: Discussionsupporting
confidence: 93%
“…Essentially this shows us that the youngest typically developing children tended to start their adjustments while further from the obstacle while the youngest children with DCD waited until they were closer. Given previous findings that children and adults with DCD start a movement adjustment earlier in the movement (Wilmut & Barnett, 2017;Wilmut et al, 2016) it is surprising that this has not also been shown in the current study. However, the previous studies have considered adjustments to movement in terms of the path of the trunk or the speed of locomotion.…”
Section: Discussioncontrasting
confidence: 64%
See 2 more Smart Citations
“…13 Maximal voluntary contraction. 14 Inter-trial intervals. 15 Bruininks-Oseretsky test of motor proficiency.…”
Section: Spect Findingsmentioning
confidence: 99%